2015
DOI: 10.1111/aji.12406
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infection‐Induced Differential Expression of LncRNAs Associated with Collagen in Mouse Placentas and Amniotic Sacs

Abstract: Our data demonstrate, for the first time, that viral infection may induce the differential expression of lncRNAs that are associated with collagen. Based on this finding, we propose that lncRNA may have involved in regulating of infection-induced collagen transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 65 publications
(93 reference statements)
1
8
0
Order By: Relevance
“…In our previous study, lncRNAs that are differentially expressed in human placentas delivered from PPROM and sPTL were found to be involved in more than 20 functional pathways (Luo et al, 2013). The patterns of differentially expressed lncRNAs and pathways identified from placentas of PPROM and sPTL were similar to those we observed in our study of human miscarriages (Wang et al, 2014) and of a viral-infected mouse model (Pan et al, 2015), suggesting that deregulation and dysfunction of the ubiquitin-proteasome-collagen (CUP) pathway may be one of the pathogenic mechanisms underlying the adverse outcomes of pregnancies, including PPROM.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…In our previous study, lncRNAs that are differentially expressed in human placentas delivered from PPROM and sPTL were found to be involved in more than 20 functional pathways (Luo et al, 2013). The patterns of differentially expressed lncRNAs and pathways identified from placentas of PPROM and sPTL were similar to those we observed in our study of human miscarriages (Wang et al, 2014) and of a viral-infected mouse model (Pan et al, 2015), suggesting that deregulation and dysfunction of the ubiquitin-proteasome-collagen (CUP) pathway may be one of the pathogenic mechanisms underlying the adverse outcomes of pregnancies, including PPROM.…”
Section: Introductionsupporting
confidence: 86%
“…The current study is a continuing investigation of the regulatory role of lncRNAs in the molecular pathogenesis of sPTB, based on our previous studies, in which we identified differential expression of lncRNAs in sPTL and PPROM (Luo et al, 2013; Pan et al, 2015). In the current study, we analyzed the DEPs of the lncRNAs and the mRNAs that are associated with the CUP pathway that may also associate with PPROM (Zhong et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, novel mechanisms in the pathogenesis of PPROM suggest the initiation of additional new research. Furthermore, our data has shown that lncRNAs associated with collagen, MMP, proteasome 26S, and ubiquitin specific peptidase were differentially expressed in placentas and amniochorionic membranes of HMV68 viral infected mice, compared to non-infected, which further indicated that there is a closed link to infection, UPS, collagen and membrane rupture [141]. Therefore, combined with the reviewed data above, a novel molecular pathogenesis of PPROM may be concluded that UPS-related lncRNAs are triggered by infection and inflammation in PPROM, which regulate intracellular and/or extracellular UPS systems to control the content of collagens in ECM, and finally result in occurrence of PPROM for the ECM degradation in fetal membrane.…”
Section: The Possible Connection Between Ups and Pprommentioning
confidence: 63%
“…25 Our earlier studies have demonstrated that transcripts including coding and long non-coding RNAs involved in the pathogenic pathway of cytokine and chemokine receptor interactions were differentially expressed and associated with early miscarriages and late preterm birth. [26][27][28][29][30] As a result, we proposed that the epigenetic regulation of the chemokine-cytokine pathway could present a common epi-pathogenic mechanism associated with variant adverse outcomes of pregnancy. 31…”
Section: Pathogenic Mechanismmentioning
confidence: 99%